Perceived Organizational Support and Proactive Innovation Behavior: The Mediating Role of Basic Psychological Needs - Fan, Chuanhao; Tang, Sijie; Chen, Long; Sun, Tingting (Frontiers in Psychology, 2022)
Drawing upon self-determination theory, this study aimed to explore the mechanisms underlying the impact of perceived organizational support on proactive innovation behavior, and reveal the serial mediation effects of basic psychological needs. We collected time-lagged date of 481 employees from research institutions in China and structural equation modelling analyses were carried out to test the hypotheses. The results indicate that perceived organizational support is significantly and positively related to proactive innovation behavior, and this relationship was mediated by the need for autonomy, competence and relatedness. These findings contribute new knowledge to proactive innovation behavior by providing a new perspective of the satisfaction of psychological needs. Theoretical and practical implications are discussed.